PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KOTA PAREPARE - Arifin, Arman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
The study is intended to gain evidence of the impact of reward and punishment on employee performance in the Secretariat Parepare Office. The data-collection techniques used in this study are questionnaires. The samples in this study number 88. Data analysis techniques in this study use computerized system analysis techniques. Partial research obtained value t count = 2.388 and its tabled t known = 1.98827 and its importance = 0.019 < 0.5. Reward (X1) affected positive and significant (Y). Simultaneously reward (X1), punishment (X2) has a positive and significant impact on employee performance (Y), which F count is 6,098 and the value of the table is 3,10, which 6,098 > 3,10.